PENGEMBANGAN ALAT UKUR SUHU UDARA DIGITAL BERBASIS MIKROKONTROLER ATMEGA32 MENGGUNAKAN SENSOR SHT75 - Nofri Hardisal (Department of Physics – Universitas Negeri Padang UNP, 2014)
Temperature is important weather parameter measured for many necessity, such as agriculture, pharmacy, and etc. In Indonesian Agency of Meteorology, Climatology and Geophysical, this parameter measured by using analog termograph with mechanic sensor is bimetal sensor. The purpose of research is development of Dygital air temperature measurement based on microcontroller Atmega32 by using SHT75 sensor with storage data in memory possesed of highest accuration and already calibrated of dygital with storage data in memory. There are three result of research such as. First, instrument built from sensor SHT75 module as sensor of temperature and box of system have 22x21x16 cm volume as place of electronic circuit. Second, data logger of instrument used internal EEPROM in Microcontroller ATMEGA32. Third, this instrument have highest precision and accuration, average of precision relative sensor SHT75 is 98,93% with average of accuration 0,999. Keyword — Alat Ukur, Suhu, Sensor SHT75